Engaging men and boys in the prevention of men's violence against women in England - BURRELL, STEPHEN,ROBERT (2019)
Efforts to engage men and boys in the prevention of men's violence against women are facing a crucial moment in England as they attract increasing societal interest. Yet there is a dearth of scholarship on this work in the English context. This study has therefore sought to build our knowledge of how practice, theory, and research on engaging men can be taken forward. Founded upon pro-feminist standpoint epistemology, it has investigated the contemporary landscape of work with men to prevent violence against women in England by conducting fourteen expert-informant interviews with key activists. In addition, it has explored how young men themselves understand and use prevention campaigns, by carrying out eight focus groups on intimate partner violence with forty-five members of men's university sports teams. These discussions underlined that more engagement with young people around gender and violence is urgently needed. The research has highlighted the contradictory nature of work with men, based as it is upon encouraging them to dismantle their own patriarchal power and privilege. It suggests that one way in which an equilibrium can be found to address these tensions is through an emphasis on men's complicity, to cultivate critical consciousness among men about their role in both perpetuating and potentially preventing violence against women. However, the focus groups illustrated that men can often respond defensively to preventative messages, by disassociating themselves from the problem for example. To help overcome these barriers, the research proposes a triadic approach to engaging men. This would involve simultaneously attending to individual men's diverse experiences and practices, the social construction of masculine norms, and the reproduction of patriarchal structural inequalities. The study concludes that if work with men can find pro-feminist balances within its contradictions in such ways, then it has significant potential to contribute towards ending violence against women